The role of the interface in a Ti‐based metallic glass matrix composite with in situ dendrite reinforcement. (2nd April 2014) - Wang, Y. S.; Hao, G. J.; Zhang, Y.; Lin, J. P.; Song, L.; Qiao, J. W.
<x xml:space="preserve">Abstract</x> Many in situ metallic glass matrix (MGM) composites have been developed as promising engineering materials having distinguished properties because of sharing virtues of high strength of metallic glasses and large plasticity of crystal phase, for example, Ti47Zr19Be15V12Cu7 MGM composites (the yield strength: 1600 MPa, the fracture strength: 3024 MPa and the total strain 32.6%). Although the toughening mechanisms in these materials have been investigated, the role of the interface bridging the ductile dendrite and the glass phase is still unclear. To this aim, specimens of the as‐received and after compression of this Ti‐based MGM composite were investigated to by using the transmission electron microscopy and the high‐resolution transmission electron microscopy. The results of the microstructure investigation indicated that the interface in the composite consists of a nanosized transform layer with an approximate width of 4 nm. During plastic deformation, the interface either suppresses plastic deformation caused by dislocations on the dendrite side or initiates nucleation of multiple shear bands throughout nanocrystallization on the glass phase side nearby the interface, which is favorable for the plastic deformation of the material. Copyright © 2014 John Wiley & Sons, Ltd.